Implementation of Web-Based E-Learning for English Language Learning in Early Childhood - Kasriyati, Destina; Suharni, Suharni; Andriani, Refika (Journal of English Education, Literature and Linguistics, 2024)
Learning English is learning that is difficult for children to understand and digest because it is a foreign language that is rarely used in everyday life. However, in this era of globalization, English is very important because it is an international language as the language of world communication. The task of the PAUD teacher is to introduce English as early as possible. This study aims to find out how the implementation of E-learning in PAUD schools in the Rumbai sub-district. This type of research is quantitative with a survey method approach. This study consisted of 14 respondents from 7 PAUD schools in the Rumbai sub-district. The results of this study used the CIPP evaluation (Context, Input, Process, Product) to measure the implementation of E-learning in PAUD schools. The result is a Context variable with a proportion of 21% in the weak category, while for the input variable with the same proportion, namely 21%, with a weak category. Furthermore, the Process variable with a proportion of 70% is in the strong category, while for the Product variable it has a proportion of 71% in the strong category. It can be concluded that the implementation of e-learning is effectively implemented even though it has obstacles.